Ophioninae (Hymenoptera: Ichneumonidae) wasp community in the cloudy forest Monteseco, Cajamarca, Peru - Sánchez, Evelyn (2014)
We describe the species composition of the subfamily Ophioninae (Hymenoptera: Ichneumonidae) along an altitudinal gradient in the cloudy forest Monteseco, Cajamarca, Peru collected in 2009 and 2010. Eighteen species were recorded in three genera of Ophioninae: Alophophion, Enicospilus y Ophion. Five species are recorded for the first time in Peru: Ophion polyhymniae Gauld, 1988; Enicospilus cubensis (Norton, 1863); E. guatemalensis (Cameron, 1886); E. cressoni Hooker, 1912 y E. mexicanus (Cresson, 1874). Subfamily composition varies with the elevation. The highest species richness (S=11) was found at 2150 m and the lowest (S=3) at 3116 m. Enicospilus is more diverse from low to mid elevation, Ophion from mid to high elevation and Alophophion occurs predominantly at high elevation.